Design and Mechanical Analysis of Bionic Foldable Beetle Wings - Caidong Wang; Chen Wang; Yu Ning; Lumin Chen; Xinjie Wang (Applied Bionics and Biomechanics)
In order to improve the flight performance of collapsible aircrafts, a novel mechanism of bionic foldable wings of beetle is designed based on the four-plate mechanism theory. The folding and unfolding movements of the bionic foldable wings are driven by motor and torsion hinges. Based on the D-H method, a kinematic model of wings is established to analyze the dihedral angle of adjacent plates. The folding ratio of an area in different plate creasing angles has been derived and calculated. Utilizing the kinematic and static models produced, as well as considering the folding ratio and output motor torque, the optimal physical parameters of folding wings are obtained. Dynamic models of rigid and flexible wings were established using ADAMS, and a motion simulation was performed. The relationship between dihedral angle and torque during the folding process of both rigid and flexible wings was obtained. The results provide a better understanding of the folding mechanism through the formulation of rigid-flexible wing analysis, as well as demonstrating a novel design of insect-mimicking artificial wings for small aerial vehicles.